Altered Protein Structures and Neoepitopes in Lupus Neutrophils From Dysregulated Splicing of Messenger RNA - Rayan Najjar; Xiaoxing Wang; Jose Mario Bello Pineda; Hugh Alessi; Alison Bays; Robert K. Bradley; James N. Jarvis; Tomas Mustelin (ACR Open Rheumatology)
Objective To test whether messenger RNA (mRNA) splicing is altered in neutrophils from patients with systemic lupus erythematosus (SLE) and can produce neoantigens. Methods RNA sequencing of neutrophils from patients with SLE (n = 15) and healthy donors (n = 12) were analyzed for mRNA splicing using the RiboSplitter pipeline, an event‐focused tool based on SplAdder with subsequent translation and protein domain annotation. RNA sequencing from SARS‐CoV2–infected individuals was used as an additional comparator. Results Neutrophils from patients with SLE contained 521 statistically significant altered mRNA splicing events compared with healthy donor neutrophils, many of them affecting important immunologic pathways, myeloid function, transcription factors, and proteins involved in mRNA splicing. A subset of splicing events were only present in SLE samples, and some of them occurred at unannotated splice acceptor or donor sites. Two patients were particularly rich in such events. Only a small number of dysregulated splicing events were more pronounced in patients with active disease or with high type I interferons but were not detected in SARS‐CoV2–infected individuals, who also had high type I interferons. Besides causing a range of structural changes, 80 mRNA splice variants exclusive to SLE were predicted to translate into novel amino acid sequences. Peptides derived from these novel amino acid sequences were predicted to bind to the individual patients’ class I and II major histocompatibility complex molecules with high affinity. Conclusion We conclude that aberrant mRNA splicing in SLE has the potential to affect both the function of granulocytes and to generate novel autoantigens.